2023
DOI: 10.3390/w15122281
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized Constructed Wetlands for Wastewater Treatment in Rural and Remote Areas of Semi-arid Regions

Abstract: Vertical-flow constructed wetlands (VFCWs) are an innovative and sustainable nature-based technology for wastewater treatment in rural areas. This work aimed to evaluate the treatment performance of VFCWs using real wastewater, which can provide more accurate and reliable results compared with field-based experiments, and to investigate the use of Paulownia trees in VFCWs for wastewater treatment. To compare the efficiency of the plants based on the treatment performance of the VFCWs, three units were prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…The use of a suitable bed fill that simultaneously provides a substrate for plant growth, along with development and physical processes, is an important issue in treatment processes. Sand and fine gravel-which are inexpensive and have good permeability and porosity-are the most common aggregates used to fill CW beds [17]. As recent studies have shown, the use of other porous materials (e.g., zeolite, clay shale, or sediments) allows for higher removal efficiencies for organic pollutants and ammoniumbased nitrogen than those in the case of conventionally filled beds [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The use of a suitable bed fill that simultaneously provides a substrate for plant growth, along with development and physical processes, is an important issue in treatment processes. Sand and fine gravel-which are inexpensive and have good permeability and porosity-are the most common aggregates used to fill CW beds [17]. As recent studies have shown, the use of other porous materials (e.g., zeolite, clay shale, or sediments) allows for higher removal efficiencies for organic pollutants and ammoniumbased nitrogen than those in the case of conventionally filled beds [18,19].…”
Section: Introductionmentioning
confidence: 99%